Anaesthesia for acute abdomen in developing countries - Yvonne O. Buowari (Healthcare in Low-resource Settings, 2014)
Acute abdomen is an emergency that requires immediate surgical intervention. In developing and low-income countries, there is limited modern drugs and medical equipment and personnel. General anaesthesia is administered for emergency abdominal surgeries. Ketamine is used in hospitals without trained personnel in the administration of anaesthesia. In other hospitals in developing countries with anaesthetist, ketamine is used for induction of anaesthesia and muscle relaxant administered to facilitate endotracheal intubation and maintain anaesthesia with inhalational agents to avoid awareness under anaesthesia.